Implementasi Metode Mccall Pada Pengujian Kualitas Website Diskominfotik Kabupaten Bengkalis - Nurul Aini; Fajar Ratnawati (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
The Communication, Informatics, and Statistics Agency (DISKOMINFOTIK) of Bengkalis is a government institution focused on information and statistics. One of the media used for information dissemination is the DISKOMINFOTIK Bengkalis website. The website of the Communication, Informatics, and Statistics Agency of Bengkalis District offers several information options such as the agency profile, work units, public information, agendas, announcements, contact details of DISKOMINFOTIK Bengkalis, as well as news published by DISKOMINFOTIK Bengkalis. Therefore, the DISKOMINFOTIK Bengkalis website is considered a significant medium for both the agency itself and the public. Hence, software quality becomes an important consideration as it directly affects the website's performance. For this reason, testing needs to be conducted on the DISKOMINFOTIK Bengkalis website. This research addresses 11 factors in McCall, namely Correctness, Reliability, Usability, Integrity, Efficiency, Reusability, Portability, Interoperability, Maintainability, Flexibility, and Testability. Testing is done in two ways: with testing tools and with questionnaires submitted to users and system developers. The results of testing conducted with questionnaires yield quality scores of Correctness 77,66%, Reliability 77,8%, Efficiency 79,01%, Integrity 77,31%, Usability 77,67%, Portability 77,31%, Maintainability 90%, Testability 90%, Flexibility 93,3%, Reusability 95%, Interoperability 90%, so the average quality is 84%.